Treatment of Decubitis Ulcer Stage IV in the Patient with Polytrauma and Vertical Share Pelvic Fracture, Diagnosed Entherocollitis and Deep Wound Infection with Clostridium Difficile with Combined Negative Pressure Wound Therapy (NPWT) and Faecal Management System: Case Report - Stojmenski, Slavcho; Merdzanovski, Igor; Gavrilovski, Andrej; Pejkova, Sofija; Dzokic, Gjorge; Tudzarova, Smilja (Open access Macedonian journal of medical sciences, 2017)
AIM: The aim of this paper was to present a case with the successful treatment of decubitis ulcer stage IV in the patient with polytrauma and vertical share pelvic fracture and diagnosed entherocollitis combined with deep wound infection with Clostridium difficile treated with combined Negative Pressure Wound Therapy (NPWT) and faecal management system.CASE REPORT: Patient D.S.1967 treated on Traumatology Clinic after tentamen suicide on 9.2.2015 with diagnosis: brain contusion; contusion of thoracal space; vertical share pelvic fracture; open fracture type II of the right calcaneus; fracture of the left calcaneus; fracture on the typical place of the left radius; fracture of the right radius with dislocation. As a first step during the treatment in Intensive care unit we perform transcondylar extension of the left leg, and in that time we cannot operate because of the brain contusion. Four weeks after this treatment we intent to perform stabilisation of the pelvic ring, fixation of both arms, and fixation of both calcanear bones. But at the time before performing the saurgery, the patient got an intensive enterocollitis from Escherichia colli and Clostridium difficile, and during the inadequate treatment of enterocollitis she got a big decubitus on both gluteal regia Grade IV and deep muscular necrosis. Several times we perform a necrectomy of necrotic tissue but the wound become bigger and the infection have a progressive intention. In that time we used VAK system for 6 weeks combined with faecal management system and with local necrectomy and system application of Antibiotics and Flagyl for enterocollitis in doses prescripted from specialists from Infective clinic. This new device to manage faecal deep decubital infection and enterocollitis with Clostridium difficile are considered as adequate. 8Flexi-Seal® FMS has been also used. After two months we succeed to minimize the gluteal wound on quoter from the situation from the beginning and we used for next two months wound treatment from Departement for Plastic and Reconstructive Surgery.CONCLUSION: When faecal incontinence as a result of enterocollitis with Clostridium difficile does occur, a limiting contact with the patient’s skin is extremely important as breakdown can occur rapidly. In addition to tissue injury, faecal incontinence can have a major impact on the patient’s dignity and result in prolonged hospital stay. The main outcomes assested in the case studies were resolution of of decubital ulcers as a result of faecal incontinence, patient comfort and ease of application of the FMS and NPWT. The soft flexible catheter was easily inserted without discomfort to the patients. It gently conformed to the rectal vault, reducing significantly the risk of necrosis, and the risk for prolonged necrosis in cases with previously developed necrosis. FMS was successful in diverting faecal fluid away from the perineal tissue and resolved any decubitus ulcer developed previously in combination with use of NPWT. So, we can recommend this combination in those cases especially with polytraumatismus, vertical share pelvis fracture combined with diarrhea and deep wound infection of decubital ulcers Grade IV infected with Cl. difficile.